Pemigatinib for the treatment of myeloid/lymphoid neoplasms with FGFR1 rearrangement. Issue 4 (3rd April 2023) - Freyer, Craig W.; Hughes, Mitchell E.; Carulli, Alison; Bagg, Adam; Hexner, Elizabeth
ABSTRACT: Introduction: Myeloid/lymphoid neoplasms with fibroblast growth factor receptor-1 ( FGFR1 ) rearrangements (MLN FGFR1 ) are rare entities with aggressive features and poor prognosis. Presentation is heterogeneous, ranging from myeloproliferative neoplasms (with or without eosinophilia) to T-cell lymphoma and acute leukemia. Historical treatments have been guided by the presenting phenotype with induction chemotherapy frequently used. Pemigatinib is a FGFR1–3 tyrosine kinase inhibitor that has demonstrated high complete hematologic and cytogenetic response rates in MLN FGFR1 . Areas covered: We discuss the pathogenesis, presentation, and historical treatments for MLN FGFR1, in addition to clinical data using pemigatinib and other targeted therapies. Discussion of the mechanism of action and adverse events is also included. Expert opinion: Pemigatinib represents a significant advance in the management of MLN FGFR1 . High rates of complete hematologic and cytogenetic response have been observed. While direct comparative data are unavailable, outcomes appear favorable compared to conventional approaches. Long-term efficacy and tolerability are not yet known, and allogeneic hematopoietic stem cell transplant (alloHSCT) continues to be the treatment with the highest chance of long-term disease free survival in responding patients. Combinations of pemigatinib and chemotherapy, particularly for more aggressive phenotypes, warrant future investigation as does the use of pemigatinib maintenance following alloHSCT.